Speciation in the "Várzéa" flooded forest: a new Mabuya (Squamata, Scincidae) from Western Amazonia - Miralles, Aurélien; Barrio-Amorós, César L.; Rivas, Gilson; Chaparro-Auza, Juan C. (Zootaxa, 2006)
Mabuya altamazonica sp. nov. is described from Peruvian Amazonia. This species is sympatric with M. nigropunctata. Despite their superficial similarity, those two Amazonian species could be differentiated both by cephalic scalation characters and molecular results (12S rRNA). Mabuya altamazonica sp. nov. differs from all Amazonian and Andean species of Mabuya by the combined presence of (1) paired prefrontals and frontoparietals, (2) a single pair of nuchals, (3) four supraoculars, (4) five subequal supraciliaries, (5) seven supralabials with the fifth being the largest and placed under the eye, (6) parietals in contact behind the interparietal and (7) dark palms and soles.